Cytotoxic Activity of Iraqi Cressa Cretica - Farah fawzi; Monther F. Mahdi; Ibrahim S. Abaas (College of Pharmacy / Mustansiriyah University, 2019)
Cressa cretica Fam: Convolvulaceae (morning glory). These plants are native to the tropical and subtropical areas of the world. Nutritional analysis provide it to be a potential source of minerals, energy, carbohydrate, alpha-tocopherol, edible oil. From phytochemical point of view, the plant was reported to contain: coumarins, sterols, alkaloids, tannins, glycosides, flavonoids, unidentified sugars and high salt content. Ethyl acetate layer and ethanolic layer were examined for cytotoxic activity.Kampferol-3-O-glucoside (Astragalin) was isolated as amorphous powder from the aerial parts of Cressa cretica. The flavonoid in the Iraqi plant was detected by TLC. Its presence was confirmed by HPLC.